2020
DOI: 10.9734/cjast/2020/v39i2530889
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Path Coefficient Analysis for ‘Yield Contributing’ Traits in Quality Protein Maize (Zea mays L.)

Abstract: Character association studies will help to assess the relationship among the yield and its components for enhancing the usefulness of the selection. In view of this, the present research work was carried out to assess the correlation coefficient and path analysis among twenty five maize genotypes using eleven quantitative parameters. Correlation studies indicated that plant height (cm), ear height (cm), ear length (cm), ear girth (cm), number of kernel rows per ear, number of kernels per row showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
3
1
0
Order By: Relevance
“…On the other hand, grain yield per hectare had either significant or highly significant positive correlation with days to 50% pollen shed, days to 50% silk, days to 100% dry husk, kernels per row, leaf area index at 60 DAS and leaf area index at 90 DAS at both phenotypic and genotypic levels while it had positive correlation with ear height only at genotypic level (Table 4). It was supported by Patil et al, [14] and Singh et al, [15] also obtain similar result. Grain yield per hectare had highly significant negative correlation with 100 kernel weight at genotypic level.…”
Section: Genotypic and Phenotypic Correlation Coefficient Across The ...supporting
confidence: 67%
“…On the other hand, grain yield per hectare had either significant or highly significant positive correlation with days to 50% pollen shed, days to 50% silk, days to 100% dry husk, kernels per row, leaf area index at 60 DAS and leaf area index at 90 DAS at both phenotypic and genotypic levels while it had positive correlation with ear height only at genotypic level (Table 4). It was supported by Patil et al, [14] and Singh et al, [15] also obtain similar result. Grain yield per hectare had highly significant negative correlation with 100 kernel weight at genotypic level.…”
Section: Genotypic and Phenotypic Correlation Coefficient Across The ...supporting
confidence: 67%
“…The observation further emphasizes the role of these three characters towards the improvement of grain yield in maize. Similar to the findings of our study, other researchers also have reported the same [12,13,14]. For determining the diversity among the inbred lines, a cluster analysis was performed, (Table 6A) which revealed that the genotypes can be classified into three clusters based on seventy percent similarity coefficient, as well as for a clear understanding, a dendogram was drawn through hierarchical cluster analysis based on unweighted pair-group method with arithmetic averages (UPGMA) and Euclidean distance (Fig.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, grain yield per plant had either significant or highly significant positive correlation with leaf area index at 60 days after sowing, kernels per row, days to 100% dry husk and grain yield per hectare at both phenotypic and genotypic levels while it had positive correlation with days to 50% pollen shed, days to 50% silking and ear height at genotypic level. Patil et al, [17] and Singh et al, [18] also obtain similar result. Grain yield per plant had highly significant negative correlation with 100 kernel weight at genotypic level.…”
Section: Genotypic and Phenotypic Correlation Coefficient During Rabi 2019-20supporting
confidence: 55%